(untitled) (Sudurpaschim Spectrum, 2026)
This research examines the extent to which age-gap romanticization in modern BookTok romance fiction contributes to the normalization of predatory dynamics. As BookTok has emerged as a powerful cultural force shaping reading habits, particularly among teenagers and young adults, it plays a significant role in popularizing romance narratives that emphasize emotional intensity and trope-driven storytelling. One such recurring trope is the age-gap romance, often involving younger female protagonists and older, more powerful male partners. Using a qualitative textual analysis of twenty popular BookTok romance novels, this study draws on feminist theory, developmental psychology, and media influence theory to examine how age, power, consent, and desire are framed within these narratives. The findings reveal consistent patterns in which youth is framed as desirability, male authority is romanticized as protection, and control is reframed as care. In particular, the analysis identifies the normalization of “predatory waiting,” where older male interest is retroactively justified once the younger character reaches legal adulthood, masking dynamics that resemble grooming or emotional conditioning. While not all age-gap romances depict harmful dynamics, the repeated romantic framing of unequal relationships, especially when amplified through BookTok’s recommendation of culture, contributes to the normalization of predatory patterns. This effect is especially concerning for younger readers who may lack the emotional maturity or critical tools needed to question such portrayals. The study concludes that age-gap romanticization in BookTok romance fiction substantially obscures structural inequalities by embedding them within emotionally appealing and culturally validated narratives, highlighting the need for greater critical engagement and media literacy.